The Process of Professional Training of Physical Training Teachers in the Countries of Europe and Ukraine - Hrynchenko, Igor (Pedagogical Discourse, 2012)
The basis of professional preparation of the future physical training teachers under the new conditions are considered in the article; the analysis of modern principles of professional training of future physical training teachers in European and Ukrainian higher educational establishments is conducted. The main approaches of introduction of pedagogical technologies including innovational ones into the process of professional training are analyzed. The necessity of system introduction of innovations in the countries of Europe and in Ukraine, new aims, content renovation,usage of new forms, means, methods of learning and teaching is underlined in the work. It also deals with the usage of renovated technological, scientific and methodical materials in the educational process of higher educational establishments